Male partner influence on family planning and contraceptive use: perspectives from community members and healthcare providers in KwaZulu-Natal, South Africa - Kriel, Yolandie; Milford, Cecilia; Cordero, Joanna; Suleman, Fatima; Beksinska, Mags; Steyn, Petrus; Smit, Jennifer Ann (Reproductive health, 2019)
Background South Africa faces numerous reproductive challenges that include high rates of unplanned and adolescent pregnancies. The uptake and utilization of family planning services and modern contraception methods depend on numerous factors. The male partner plays a key role in reproductive health but data on this topic are outdated or have a predominant HIV prevention focus. The purpose of this paper is to explore the influence of male partners on family planning and contraceptive (FP/C) uptake and use within the contemporary South African setting, and to identify further areas of exploration. Methods This qualitative study was conducted in a community and healthcare provision setting in the eThekwini District in KwaZulu-Natal province, South Africa. Data were collected from twelve community-based focus group discussions ( n = 103), two healthcare providers focus group discussions ( n = 16), and eight key informant individual in-depth interviews. Following a constructionist paradigm and using the health utilization behaviour model, data were analysed using thematic analysis, allowing a robust and holistic exploration of the data. Results The data from this study revealed the complex and evolving role that male partners play in FP/C uptake and use within this setting. Key themes from the data elucidated the dual nature of male involvement in FP/C use. Culturally influenced gender dynamics and adequate understanding of FP/C information were highlighted as key factors that influenced male attitudes and perceptions about contraceptive use, whether positively or negatively. Male opposition was attributed to limited understanding; misunderstandings about side-effects; male dominance in relationships; and physical abuse. These factors contributed to covert or discontinued use by female partners. Pathways identified through which male partners positively influenced FP/C uptake and access include: social support, adequate information, and shared responsibility. Conclusions Understanding the role that male partners play in FP/C uptake and use is important in preventing unintended pregnancies and improving family planning policy and service delivery programmes. By identifying the barriers that male partners present, appropriate strategies can be implemented. Equally important is identifying how male partners facilitate and promote adherence and use, and how these positive strategies can be incorporated into policy to improve the uptake and use of FP/C.